The moderating effect of convenience towards the relationship between satisfaction and loyalty in Malaysian banking industry - Ali, Norhidayah; Mohd Noor, Nor Azila; Mahmood, Rosli (MCSER Publishing, Rome-Italy, 2016)
The aim of this research was to explore the influence of e-satisfaction towards e-loyalty among the internet banking users in Malaysia. The moderating effect of convenience on the relationship between e-satisfaction and e-loyalty was also analysed.The study employed systematic sampling technique to recruit respondents. Intercept survey was chosen as method of data collection in which a 25-item questionnaire was used to measure respondents’ e-satisfaction (5 items), e-loyalty (13 items) and convenience (7 items).The survey yielded 120 usable responses. Data were analysed using variance-based partial least squares (PLS) structural equation modelling advanced statistical technique with the help of Smart-PLS version 3. PLS, which has become popular in marketing and social science research, was used to determine the factor loadings and path coefficients in the theoretical model. The study has concluded that e-satisfaction has an effect on e-loyalty; however the moderation effect of convenience was not significant.